Manufacturing processes and systems : selected, peer reviewed papers from the 2010 International Conference on Advances in Materials and Manufacturing Processes (ICAMMP 2010), 6-8 November, 2010, Shenzhen, China - Liu, Xianghua; Jiang, Zhengyi; Han, Jingtao (Advanced materials research ;, 2010)
"This book aims to collect the latest advancement and applications of computer numerical control systems, operations planning, geometric dimensioning and tolerancing, quality systems, basic machine tool elements, process automation, operator-machine systems, cost estimating, metrology and testing, etc."--Preface